DONORS (Donation Network to Optimise Organ Recovery Study): Study protocol to evaluate the implementation of an evidence-based checklist for brain-dead potential organ donor management in intensive care units, a cluster randomised trial. Issue 6 (25th June 2019) - Westphal, Glauco Adrieno; Robinson, Caroline Cabral; Biasi, Alexandre; Machado, Flávia Ribeiro; Rosa, Regis Goulart; Teixeira, Cassiano; de Andrade, Joel; Franke, Cristiano Augusto; Azevedo, Luciano Cesar Pontes; Bozza, Fernando; Guterres, Cátia Moreira; da Silva, Daiana Barbosa; et al.
Abstract : Introduction: There is an increasing demand for multi-organ donors for organ transplantation programmes. This study protocol describes the Donation Network to Optimise Organ Recovery Study, a planned cluster randomised controlled trial that aims to evaluate the effectiveness of the implementation of an evidence-based, goal-directed checklist for brain-dead potential organ donor management in intensive care units (ICUs) in reducing the loss of potential donors due to cardiac arrest. Methods and analysis: The study will include ICUs of at least 60 Brazilian sites with an average of ≥10 annual notifications of valid potential organ donors. Hospitals will be randomly assigned (with a 1:1 allocation ratio) to the intervention group, which will involve the implementation of an evidence-based, goal-directed checklist for potential organ donor maintenance, or the control group, which will maintain the usual care practices of the ICU. Team members from all participating ICUs will receive training on how to conduct family interviews for organ donation. The primary outcome will be loss of potential donors due to cardiac arrest. Secondary outcomes will include the number of actual organ donors and the number of organs recovered per actual donor. Ethics and dissemination: The institutional review board (IRB) of the coordinating centre and of each participating site individually approved the study. We requested a waiver of informed consent for the IRB of each site. Study results will be disseminated to the general medical community through publications in peer-reviewed medical journals. Trial registration number: NCT03179020 ; Pre-results.